Pengaruh Penambahan Molase pada produksi Bioethanol dari Limbah Padat Industri Pati Aren - Dewi Astuti Herawati; Andang Arif Wibawa (Biomedika, 2019)
Research has been carried out to determine the effect of the addition of molasses to on bioethanol production from palm starch industrial solid waste. The stages of this research were the preparation of raw materials, delignification of palm starch solid waste, lignin content analysis, enzyme production, anaerobic fermentation and ethanol content analysis. Delignification of palm starch solid waste using 3% NaOH solution. Enzyme production is produced from A. Niger and Trichoderma sp. Fermentation using 5 grams of delignified sample added a nutrient solution, a mixture of cellulase enzymes from A. niger and Trichoderma sp. by comparison (1: 2), molasses and Saccharomyces cereviseae. Analysis of ethanol levels was carried out every day until the 6th day. Delignification using 3% NaOH solution can reduce the level of lignin samples up to 17.15%. The addition of molasses containing 35% sugar as a source of sugar in the palm starch solid waste will increase the levels of bioethanol from 0.0904% to 3, 5407%, whereas molasses with 40% sugar content results in lower bioethanol levels. The higher the sugar content, the higher the level of bioethanol, but if the sugar content is too concentrated, it causes a slow fermentation process in the production of bioethanol.